Design, technological and ecological aspects of designing and realization of technology manufacturing powder compositions materials and products - B.C. MESHI; A.V. LYULKO; M.P. DRYAGINA; A.V. TRIFONOV (Advanced Engineering Research, 2008)
Set of the created design and technology and predicted ecological circumstances, and also the existing and accessible specialized manufacture of unique production - iron powders of different quality and properties, and also high universality and a good adaptability of powder metallurgy technology to application in various areas of technics (technical equipment), the high rational factor « quality/ price » make technology of composites economically, technologically and ecologically attractive.